COUGH PHYTOTHERAPY IN CHILDREN - L. R. Selimzyanova; E. A. Promyslova; E. A. Vishneva (Union of pediatricians of Russia, 2013)
Cough is one of the most widespread causes of outpatient pediatrician's visits. There has been a notable increase in the use of phytogenic drugs recently, including treatment of respiratory infections in children. The article examines physiological and pathological effects of cough. Issues of phytotherapy efficiency and safety are covered. Data on the use of phytogenic drugs in the treatment of respiratory diseases are presented.